STRATEGI PEMASARAN MEDIA ONLINE TERHADAP PEDAGANG KAKI LIMA DI PASAR SENTRAL KOTA MAKASSAR - Abd. Rahman; Jusman Jusman; Sitti Sahara Syamel; Hermawati Mappiwali; Muh. Fachrur Razy Mahka (Jurnal Abdimas Bina Bangsa, 2023)
This PKM aims to identify and analyze effective online media marketing strategies to help increase the competitiveness of street vendors in the Makassar City Central Market. The Central Market is one of the important traditional trading centers in the region, but street vendors in the market still face various obstacles in expanding their reach and increasing their income. This devotion uses a persuasive approach through training. The survey was conducted to identify the level of use of information technology and online media among street vendors, as well as the barriers they face in adopting online media marketing strategies. Data was also collected through in-depth interviews with a number of street vendors who have successfully implemented online media marketing effectively